Evaluating the biological characteristics of targeted ZIF-8-encapsulated individual and combined drug systems for enhanced in vivo toxicity mitigation using folic acid ligands - Sadeq, Noor S.; Masarudin, Mas Jaffri; Abdul Rahman, Mohd Basyaruddin; Chia, Suet Lin; Ahmad, Syahida; Ahmad, Haslina (Royal Society of Chemistry, 2026)
The management of toxicity, and the fulfillment of safety requirements are considered as the most prominent challenges associated with cancer drug delivery. This study introduces a novel pH-responsive nanoparticle system based on ZIF-8 for the co-delivery of a ruthenium(ii) polypyridyl complex (RuPIP) and olaparib (Olap), which is designed for enhanced therapeutic efficacy and reduced systematic toxicity. To improve their biocompatibility and targeting, the nanoparticles were surface-coated with folic acid ligand, yielding the final RuPIP–Olap@ZIF-8-FA formulation. The RuPIP–Olap@ZIF-8 nanoparticles were fabricated through a rapid, eco-friendly method, and they achieved high co-loading capacities of 20.59% ± 1.38% for RuPIP and 10.77% ± 1.00% for Olap, as confirmed by HPLC analysis. In vitro, the FA-coated dual-drug system exhibited clear pH-responsive behaviour, releasing 80% of RuPIP and 99% of Olap at pH 5.0, compared with 32% and 29%, respectively, at pH 7.4 within 48 hours. The FA-coated RuPIP–Olap@ZIF-8 system also showed markedly enhanced cytotoxicity against the MCF-7 and MDA-MB-231 cell lines, reducing the cell viability to 11.38% and 13.48%, respectively. In comparison to the non-coated dual-drug system, the FA-coated dual-drug system did not induce lethality to 75% of embryos (LC50 > 250 µg mL−1) with significant improved survivability (90%) until 120 h of incubation. Results showed that RuPIP–Olap@ZIF8-FA did not cause significant malformations, even at elevated concentrations, and did not present aggregation issues toward healthy embryos. These findings establish RuPIP–Olap@ZIF-8-FA as a promising dual-drug nanocarrier capable of targeted delivery, pH-triggered release, and distinct therapeutic pathways. Its high loading efficiency, simplicity, and improved safety profile highlight its strong potential for advancement toward clinical translation.